2013
DOI: 10.1111/trf.12099
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive pH monitoring of platelet concentrates: a large field test

Abstract: In this setting where the vast majority of PCs were of good quality and within acceptable pH limits, daily, noninvasive routine pH measurement has limited added value in identifying quality-compromised PCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…More recently, a field trial was conducted at the Sanquin Blood Bank that monitored the pH of 13,693 PLT units utilizing the pH SAFE technology. It was shown that units with positive bacterial contamination had a more rapid decline in pH than noncontaminated units …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a field trial was conducted at the Sanquin Blood Bank that monitored the pH of 13,693 PLT units utilizing the pH SAFE technology. It was shown that units with positive bacterial contamination had a more rapid decline in pH than noncontaminated units …”
Section: Discussionmentioning
confidence: 99%
“…Upon receiving the PCs in Ottawa, the sterility of the units was confirmed with the BacT/ALERT system as previously described . The pH was then measured using the pH SAFE reader as described by Gkoumassi and coworkers . Briefly, pH SAFE PC bags have a small sensor tube welded in the rim.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Products with macroaggregates or clumps may be discarded due to concerns linked to efficacy and safety of the product. Discard may occur at different occasions, for example, at the blood centre when staff notice irreversible clumps, in the hospital blood bank when clumps are missed by the blood centre or form on blood bank shelves, or on the hospital ward when clumps are missed by the blood bank staff or form during transport to the ward . Currently there is no consensus on a general discard strategy and procedures therefore vary from centre to centre.…”
Section: Introductionmentioning
confidence: 99%
“…This sensor comprises a pH-sensitive fluorescent membrane fixed to a clear window inside a small sensor tube, which is welded in the rim of the PC container. Fluorescence of the sensor membrane is measured through the window using a fiber optic probe and the BCSI pH SAFE reader calculates pH based on the ratio of yellow and red fluorescence measured [61,62]. Preliminary studies by Montag et al [63] demonstrated a decrease of pH (6.7 to 6.5) in bacterially contaminated units after reaching high bacterial counts.…”
Section: Diagnostic Methods - Bacterial Screening Strategiesmentioning
confidence: 99%